Climbing without a ladder: A proposed Professional Standards Framework for Academic Language and Learning Educators - Mister, Bianca; Simelane, Portia; Dzator, Michael (Journal of Academic Language and Learning, 2026)
Academic Language and Learning (ALL) educators work across a variety of Australian higher education institutions, playing a critical role in developing students’ academic language. The importance of these roles has been amplified in light of sector-wide efforts to improve academic language and learning, leading to student success. Yet, despite the clear contribution ALL educators make to the student experience, their professional status remains ambiguous, and their career progression pathways are often unclear. The work they do is situated in centralised learning support units, but in some cases, ALL educators are embedded within faculties or work in close collaboration with academic teaching staff. This inconsistency in terms of where ALL educators are situated reflects a broader lack of shared understanding regarding the role’s scope and identity. The present study investigates how ALL educators are positioned within the Australian higher education landscape and how the profession is defined, recognised, and supported across institutions, with attention to how expertise is valued, and career progression unfolds in practice. The analysis draws on data derived from 31 Australian Universities’ websites, job descriptions and LinkedIn profiles to examine the qualifications, skills, and career trajectories of professionals in ALL educator roles across the sector. The paper finishes with a proposed Professional Standards Framework for ALL educators to support consistent role definition, professional development, and career advancement.